Study of solution combustion synthesis in accelerated rate adiabatic calorimetry for making nickel nanoparticles - Anchu Ashok (14152020) (2025)
One approach to minimize the safety hazard of the explosive chemistry of solution combustion synthesis (SCS) is to conduct the synthesis in a closed reactor system. To design such a reactor, it is essential to get full information about the reaction heat release with the associated temperature and pressure evolution profile. A pseudo-adiabatic calorimeter was used to understand the chemistry and heat release from SCS. The reaction chemistry of a nickel (Ni) nitrate-fuel mixture for the synthesis of Ni nanoparticles at different quantities of the reactive mixture, fuel to metal ratio (φ) and various fuel types in a closed calorimetry cell was studied. As the amount of fuel changed, a discontinuity in the heating rate profile was observed, suggesting a change in the reaction mechanism(s) to a very violent and energetic phenomenon such as those observed for organic peroxides. The choice of fuel had a significant influence on the rate of temperature and pressure change with glycine exhibiting the highest rates. Overall, significant differences in the crystalline phase, morphology, and surface elemental composition of the nanoparticles produced in a closed environment as compared with the ones produced in open ones were observed. Other Information Published in: Process Safety and Environmental Protection License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.psep.2025.107476